2023
DOI: 10.1002/jsfa.12890
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic study on the inhibition of α‐amylase and α‐glucosidase using the extract of ultrasound‐treated coffee leaves

Yu Sun,
Qingwei Cao,
Yuanyuan Huang
et al.

Abstract: BackgroundOur previous studies have shown that ultrasound‐treated γ‐aminobutyric acid (GABA)‐rich coffee leaves have higher angiotensin‐I‐converting enzyme inhibitory activity than their untreated counterpart. However, whether they have antidiabetic activity remains unknown. In this study, we aimed to investigate the inhibitory activities of coffee leaf extracts (CLEs) prepared with ultrasound (CLE‐U) or without ultrasound (CLE‐NU) pretreatment on α‐amylase and α‐glucosidase. Subsequently, we evaluated the bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…A study conducted in our laboratory employing molecular docking exhibited that 5‐CQA, 3, 5‐diCQA, mangiferin, rutin, GABA, caffeine, and trigonelline can bind to the amino acid residues located outside the active site of α‐glucosidase (Sun et al. 2023). This result indicated that they could potentially serve as inhibitors for α‐glucosidase found in the extract or kombucha prepared from coffee leaves.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study conducted in our laboratory employing molecular docking exhibited that 5‐CQA, 3, 5‐diCQA, mangiferin, rutin, GABA, caffeine, and trigonelline can bind to the amino acid residues located outside the active site of α‐glucosidase (Sun et al. 2023). This result indicated that they could potentially serve as inhibitors for α‐glucosidase found in the extract or kombucha prepared from coffee leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, other studies reported that polyphenols, polysaccharides, flavonoids, tannin, quercetin, ursolic acid, anthocyanin, and procyanidins are potential inhibitors against α-glucosidase (Hossain et al, 2020). A study conducted in our laboratory employing molecular docking exhibited that 5-CQA, 3, 5-diCQA, mangiferin, rutin, GABA, caffeine, and trigonelline can bind to the amino acid residues located outside the active site of α-glucosidase (Sun et al 2023). This result indicated that they could potentially serve as inhibitors for α-glucosidase found in the extract or kombucha prepared from coffee leaves.…”
Section: Antioxidant Activity and α-Glucosidase Inhibitory Activity O...mentioning
confidence: 92%
See 1 more Smart Citation
“…The preparation of ultrasound‐induced GABA‐enriched coffee leaves and the CLE was carried out according to the method described in our previous study (Sun et al., 2023). The CLE prepared by the coffee leaves with or without ultrasound treatment was named CLE‐U and CLE‐NU, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…GABA is an inhibitory neurotransmitter with a variety of bioactive functions, such as antidiabetic, antioxidant, and antihypertensive (Sun, Mehmood et al., 2022). Furthermore, our previous study revealed that ultrasound‐induced GABA‐enriched coffee leaf extract (CLE‐U) displayed higher inhibitory activity against α‐glucosidase and α‐amylase compared to its untreated counterpart (CLE‐NU) (Sun et al., 2023). However, the potential of CLE to impede the formation of AGEs and their precursors remains unexplored, as does the differentiation in inhibitory efficacy between CLE‐U and CLE‐NU, along with the underlying mechanisms governing this phenomenon.…”
Section: Introductionmentioning
confidence: 99%